(3cJGH GHdhfjhS aj bWY GdNWhW Ydi GdfSHs - (3GHdhfjhSs ((3OeTb s)
(3ChdgG (B:s
(3HYO GdHSedI hGdOjHGLI EPG cGf NWG aj ehVhYGf aj SWM hgeG ZjQ eJfGgHjf hcGf eJhGRfjf Gh eJbGWYjf hJYde Ydi cd hGMO efgeG fbWI s
(3BNQgG (B:s
(3ef BNQ GdehLhO Hg GdQGHY GdfSHI GdYXje abO jecf Cf JNQL ef fbWI NWG jbWY s
(3Vef eLehY , JQJjHgG (B: 1s
(3HgG fXGe GdJYbjHIs
(3bQf GdfSN (B:s
(3GdbQf GdNGeSs
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ , JGeI s
(3MGdI GdfSNI LjOI s
Keywords: (3GdQjGVjGJs